A Test in a High Altitude Lake of a Multi-Parametric Rapid Methodology for Assessing Life in Liquid Environments on Planetary Bodies: A Potential New Freshwater Polychaete Tubeworm Community - Tilot, Virginie C.; Cabrol, Nathalie A.; Parro, Victor; Fairén, Alberto G.; Ormond, Rupert F. G.; Moreno-Ostos, Enrique; Lopez-Gonzalez, Nieves; Figueroa, Fabián A.; Gallardo-Carreño, Ignacio; Smith, Eric W.; Sobrón, Pablo; Demergasso, Cecilia; et al. (Frontiers in Environmental Science, 2019)
On our planet, aqueous environments such as deep sea or high-altitude aphotic lakes, subject to present or past volcanic activity and active deglaciation, may provide analogues to the aqueous environments found on such planetary bodies as Europa, Titan or Enceladus. We report here methodologies and technologies tested in Laguna Negra, a high altitude lake in the Central Andes, Chile, for exploring and assessing the presence of life within planetary lakes or interior oceans. We adopted a multi-parametric Rapid Ecological Assessment (REA) approach centered around collecting video imagery (by an Underwater Imaging System) and sampling benthic sediments (for sedimentological, biological and geochemical analysis) to depths of 272 m, to complement physico-chemical sampling of the water column and collection of shallow sediments for microbiological analysis (reported in separate publications). This enabled us to classify and assess the apparent status of benthic habitats, based on substrata and environmental characteristics, together with floral and faunal community characteristics and bioturbation artifacts. Videos imagery showed that the lower water column was characterized by a variably intense sestonic flux of particles and debris among which were planktonic organisms such as ostracods, copepods and possibly cladocerans. Sediment analysis revealed at all depths abundant diatom frustules, mainly of an acidophile pennade diatom Pinnularia acidicola, amid vegetal debris likely originating from littoral macrophytes. Video imagery showed that the lakebed was partly covered by microbial mats and depositional matter and harboured an unexpectedly rich assortment of macrofauna, including sponges, tubificid worms, flatworms, bivalves and crustaceans. Various forms of bioturbation were also encountered, some with the animals in the tracks. Most notably, at the deepest site, a previously undescribed faunal feature was evident, apparently formed by a mat-like community of several layers of what appeared to be polychaete tubeworms, possibly of the family Siboglinidae. It is hypothesized that the hydrothermal activity observed in the region may supply the compounds able to support the deep-water microrganisms from which such tubeworms typically gain sustenance. Such processes could be present on other deep and aphotic liquid-water-bearing planetary bodies.